"Tropical" Architecture in the Highlands of Southeast Asia: Tropicality, Modernity and Identity. Issue 2 (4th May 2017) - Beynon, David
Abstract: The "tropical" condition has long been established as a Western trope that defines the "otherness" of climates perceived as hot, humid and uncomfortable compared to the "temperate" West. Both colonial adaptations and "Tropical Modernist" architectural responses to Southeast Asian locations were primarily framed in terms of their amelioration of this apparently hostile environment. That the more recent conflations of tropicality with postcolonial Asian identity and environmental sustainability remain within the same construct leads to questions not only of what architectural alternatives there might be, but also what alternative tropicalities there might be. This paper explores the possibilities suggested by contemporary buildings in Southeast Asia's tropical highlands. Produced in the relative absence of "tropical" imperatives and the presence of long-standing traditions of autonomy and resistance to lowland state formations, this architecture offers a less homogenous reading of tropicality.